Analysis of Commercial Milk Samples Present in Pakistani Markets - Siddique, Anam; Ikram Aujla, Muhammad; Ahmed, Dildar (Asian Journal of Chemistry, 2012)
Milk is the first choice diet for persons belonging to all age groups. Milk is available in the market in its fresh form and in the packed form. Analysis of packed milks available in Pakistan (Lahore) market was carried for this research work. More than 100 different components have been identified in cow's milk. Most selling brands including Nurpur, Haleeb, Olper's, good milk, milk pack, dairy queen, Gournmet milk were obtained from the market and open raw milk was obtained from milkman. Energy values of the samples were compared on the basis of their fat contents. Similarly smaller will be the chain of fatty acids, greater will be the sponification number. According to this good milk contained greater amount of energy and Gournmet Bakers milk contained lesser amount of energy as it indicated lesser per cent of fats. Similarly Nurpur milk gave smaller amount of sponification number so it contained longer fatty acids chain. The milk sample like Olpher, which contained smaller fatty chain as it contained greater sponification number. Out of these eight milk samples milk pack contains all the nutrition values that meet with the ideal milk to drink. Other milk samples like good milk, Olper's and Nurpur was also quite good and meet nearly with the requirements.